al-Tafsir al-Tawhidi : a study on the ideological aspect of Hasan al-Turabi's exegetical work - Ibrahim, Esam Eltigani Mohamed (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
Dr. Hasan al-Turabi is considered one of the eminent figures in international Islamic movement and one of its most influential as well as controversial thinkers. He authored numerous books in the field of Islamic Studies; among the most prominent and recent is his Qur'anic exegesis entitled “al-Tafsir al-Tawhidi”. This research aims to study the ideological aspects of al-Turabi's exegetical work by outlining his ideology, and explaining its impact on his exegesis methodology. Furthermore, the research discusses the general intellectual theory of al-Turabi, and the axis and fundamental ideological rules of his exegesis. The research relies on analytic and inductive methodologies to reach the desired results. One of these results is that Tawhid, which focuses on renewing the Islamic religion and the establishment of the Islamic State, represents the general ideological theory of al-Turabi and the foundation of his exegesis. The study also points out that the methodology followed in al-Tafsir al-Tawhidi is an ideological methodology that rendered the Qur'an as a subordinate, and ignored the sunnah of the Prophet as a primary source in exegesis. The research also reveals that al-Tafsir al-Tawhidi can be classified among the modernist exegetical trend (al-itijah al-hadathi fi al-tafsir) as it claims that the Qur'an is open to personal interpretation and cannot be limited to specific meaning, it marginalizes the understanding of the Prophet and previous scholars to the Qur'an, and it claims the historicity of the sunnah of the Prophet and the understanding of the Qur'an. Furthermore, al-Tafsir al-Tawhidi excelled in logically connecting the meanings of the verses and surahs of the Qur'an in such a way that they bind coherently throughout the Qur'an.